2020
DOI: 10.1080/09064702.2020.1737215
|View full text |Cite
|
Sign up to set email alerts
|

Propionic acid bacteria enhance ruminal feed degradation and reduce methane production in vitro

Abstract: Thirty-one strains of propionic acid bacteria were screened for their effects on methane production and volatile fatty acid concentrations using in vitro assays of rumen fluid from Norwegian dairy cows and a grass silage-concentrate mixture as substrate. Nine of 31 strains were further analysed for effects on substrate degradation. Propionic acid bacteria led to reductions of up to 20% in methane production. Seven strains stimulated volatile fatty acid production, and in their presence in vitro substrate degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Introducing propionate-producing bacteria has been evaluated as a possible solution because propionate production consumes H 2 as a reducing equivalent and, thereby, competes with methanogenesis (Ungerfeld 2013). This has not been effective with all strains of bacteria but Propionibacterium thoenii T159 reduced CH 4 production by 20% and increased VFA production by 21% in a study that screened 31 different strains within in vitro models (Chen et al 2020). However, in lactating primiparous cows, P. freudenreichii 53-W was shown to increase CH 4 production by 27% (Jeyanathan et al 2019).…”
Section: Probioticsmentioning
confidence: 99%
“…Introducing propionate-producing bacteria has been evaluated as a possible solution because propionate production consumes H 2 as a reducing equivalent and, thereby, competes with methanogenesis (Ungerfeld 2013). This has not been effective with all strains of bacteria but Propionibacterium thoenii T159 reduced CH 4 production by 20% and increased VFA production by 21% in a study that screened 31 different strains within in vitro models (Chen et al 2020). However, in lactating primiparous cows, P. freudenreichii 53-W was shown to increase CH 4 production by 27% (Jeyanathan et al 2019).…”
Section: Probioticsmentioning
confidence: 99%
“…Propionic acid has prebiotic properties which stimulate the development of normal intestinal microflora (Radzikowski, 2018). The rumen microflora is a crucial in ruminant digestion as well as propionate fermentation in ruminants might lower methane emissions (Matthews et al, 2018;Chen et al, 2020).…”
Section: Rural Sustainability Research 44(339) 2020mentioning
confidence: 99%
“…The rumen microbial community predominantly consists of bacteria, in addition to fungi, protozoa, and a small number of phages (Miller et al, 2012), with each microorganism in a dynamic balance of competition and coordination. Several studies have shown that rumen microorganisms are closely linked to the ruminant livestock production efficiency and provide the host with as much as 65-75% of its energy requirement through anaerobic fermentation (Jewell et al, 2015;Chen et al, 2020). The rumen microbial community structure is affected by factors such as host type, health, and diet, and consequently, it varies across different regions and seasons (Yáñez-Ruiz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%